Heading out to wonderful ebook - Goolrick, Robert (2013)
It is the summer of 1948 when a handsome, charismatic stranger, Charlie Beale, recently back from the war in Europe, shows up in the town of Brownsburg, a sleepy village nestled in the Valley of Virginia. All he has with him are two suitcases: one contains his few possessions, including a fine set of butcher knives; the other is full of money. A lot of money. Heading Out to Wonderful is a haunting, heart-stopping novel of love gone terribly wrong in a place where once upon a time such things could happen.